2022
DOI: 10.15407/mfint.44.12.1679
|View full text |Cite
|
Sign up to set email alerts
|

Development of Set of Requirements for Methods of Evaluating Performance of Welded Joints ‘Base–Overlay Metal’ from Nickel-Based Superalloys of ZhS6 and ZhS32 Type Simulating Repairing of Aircraft Gas Turbine Engines Blade Edges under Industrial Conditions

Abstract: Наведено результати досліджень мікроструктури та механічних властивостей зварних з'єднань «основний-натоплений метал» ніклевих жароміцних стопів ЖС6 і ЖС32 із вмістом зміцнювальної γ′-фази орієнтовно у 60 об.%, одержаних мікроплазмовим порошковим натопленням, і порівняно їх з аналогічними опублікованими ФГУП «ВИАМ» ГНЦ рф даними стосовно натопленого металу ЖС32, одержаного способом селективного лазерного стоплення. Встановлено, що механічні властивості натопленого металу типу ЖС6У і ЖС32 характеризуються низьк… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Research results [56] showed that to extend the life cycle of gas turbine engines, it is advisable to use surfacing to restore worn parts from heatresistant nickel alloys. Rationally selecting heatresistant alloys for the manufacture of parts and operating modes, it is possible to increase the resource of gas turbine engines [57] and their environmental friendliness [58].…”
Section: Resultsmentioning
confidence: 99%
“…Research results [56] showed that to extend the life cycle of gas turbine engines, it is advisable to use surfacing to restore worn parts from heatresistant nickel alloys. Rationally selecting heatresistant alloys for the manufacture of parts and operating modes, it is possible to increase the resource of gas turbine engines [57] and their environmental friendliness [58].…”
Section: Resultsmentioning
confidence: 99%